IMPLEMENTASI PROGRAM TAḤFIẒ AL-QUR’AN SEMESTER GENAP TAHUN AJARAN 2017/2018 DI KELAS 1 C MIN 1 YOGYAKARTA - Khodijah Noor Rahmawati; Nur Hidayat (JMIE (Journal of Madrasah Ibtidaiyah Education), 2019)
Seeing the reality of this modern age, many influences of technology and play facilities are increasingly diverse, so it is not easy to raise awareness for Muslims, especially children to memorize the Qur'an, because it would be easier if memorizing the Koran began early age, so that the child will more quickly absorb the memory to achieve the expected memorization, then a place is needed to motivate and memorize the Qur'an. One of the schools that teaches the taḥfiẓ al-Qur'an program is class 1 C MIN 1 Yogyakarta. The objectives of this study are: (1) To find out the implementation of taḥfiẓ al-Qur'an learning program in the semester of 2017/2018 academic year in class 1 C MIN 1 Yogyakarta, (2) To find out the methods used in taḥfiẓ al-Qur'an learning even semester 2017/2018 academic year in class 1 C MIN 1 Yogyakarta, (3) To find out the supporting and inhibiting factors of ta'fi learning al-Qur'an the even semester of the academic year 2017/2018 in class 1 C MIN 1 Yogyakarta. This study uses a qualitative approach. The research subjects were class teachers and first grade students of C MIN 1 Yogyakarta, the object of this research was the implementation of the Qur'anic ta'fi program in class 1 C. data collection in this study through observation, interviews and documentation studies, and based on the data obtained the author of the analysis by focusing on things that are the subject of discussion, triangulation of data and drawing conclusions.        Based on the results of the research in the field the authors obtained findings including: (1) the background of the program taḥfiḥ al-Qur'an in class 1 C MIN 1 Yogyakarta, namely the demands of the times and needs of class, parents, and students; (2) the aim of the taḥfiẓ al-Qur'an program is to print the memorizing generation of the Qur'an early; (3) taḥfiḥ program is required for class 1 C with the target of memorizing juz 30 in odd semester and selected letters in even semester; (4) material covering juz 30 and selected letters chosen by the class teacher; (5) the scoring system in the form of daily deposits and financial examinations; (6) taḥfi pembelajaran learning process includes opening, muraja'ah, adding memorization, deposit and closing; (7) the methods used are Bī al-Nażar, Takrīr, Jama ’, Ṣima'i and Talaqqī; (8) supporting factors include student motivation and interest, use of mental rhythms, teacher attention, conducive time and appreciation for students who have passed memorization; (9) inhibiting factors, namely the ability of different students, less able to manage time, lack of parental attention and almost the same.